تأثير الفكر العربي والغربي في الأدب الملايوي - Yaacob, Adli (2014)
This article is an attempt to study the influence of Arabic and English on Malay language and literature. Arabic took precedence over English in influencing Malay language with loan words and the use of its letters. This was also the result of the efforts of Malay scholars such as Sheikh Daud al-Fatani, Sheikh Ahmad al-Fatani, Sheikh Abdul Samad al-Palembangi, Tol Kenali and others. During the British colonial period, English was given the focus in education and as a result to that, Malays who studied at the British oriented schools tend to diminish the influence of Arabic from the life sphere of the Malays. The influence of English began to weaken the position of Arabic in the Malay culture by the emergence of the perception that the Western culture is more superior than the local Islamic one. The change was drastic, many English educated Malay were becoming more vocal to use the Roman alphabet to replace the Arabic scripts. The main proponents to this campaign was ‘Abdullah Munshi’. On the other hand, scholar such as Zaaba who had both types of Education, English and local Islamic background was struggling to hang on to whatever is left of the Arabic influence on Malay; he was trying to produce grammar for Malay based on Arabic. Western influence on Malay extended also to literature such as the emergence of the writing of short stories and novels. Key words: Influence, Language, literature, scholars, culture